Uncertainty Reduction Theory dalam Pola Komunikasi Pemain dan Pelatih Sepakbola Usia Dini di PFA (Pasoepati Football Academy) - Arif Nugrahadi (Universitas Ahmad Dahlan, 2019)
Communication at the beginning of the meeting is a key communication that will be a benchmark for the relationship between future interpersonal communication that will be undertaken by those who communicate. A sense of uncertainty and anxiety will arise when we do not know the information about our interlocutors who encourage us to do things that will reduce the sense of uncertainty. Inhibiting factors from inside and outside of people whoÂ communicate are very influential in the emergence of uncertainty and anxiety. Moreover, this study examines early childhood who are ill in the developing ages in their environment. This study aims to determine the type of uncertaintyexperienced by early football players and coaches Pasoepati Football academyand how their rategies in reducing uncertainty through Charles Bergerâ€™stheory of uncertainty reduction. The researcher used a qualitative descriptive method by conducting in-depth interviews with players and PaseopathicFootball Academy coaches. This udy shows that the uncertainty experiencedby players and coaches is cognitive uncertainty, and for uncertainty reductionrategies using active, passive, and interactive strategies.